USE OF DIALOGUE AND POLYLOGUE IN FOREIGN LANGUAGE LESSONS (Scientific journal of the Fergana State University, 2024)
This article is about the use of monologue, dialogue and polylogue forms of oral speech in foreign language classes. The article describes the differences between dialogic and monologue types of speech, the difficulties of learning them and ways to overcome them. Students studying a foreign language in their specialty are recommended to use dialogic types of speech - information exchange speech, planning speech, discussion speech. The article also discusses the features of polylogue - a type of speech used to develop students' ability to conduct a discussion in a foreign language. Polylogue is important for expanding the critical thinking of students, in contrast to communicative dialogue, with polylogue communication the speech act is directed not only at one recipient, but also at all listeners.